The relationship between diabetes and depressive symptoms in men with or at risk of HIV infection. Issue 1 (24th September 2020) - Basil, RC; Brown, TT; Haberlen, S; Rubin, LH; Plankey, M; Becker, JT; Lake, JE; Palella, FJ; Sarkar, S
Abstract : Objectives: The aim of the study was to compare the prevalence of comorbid diabetes and depressive symptoms in men living with HIV (MLWH) with that in men without HIV infection and to determine associations between glycaemic control and depressive symptoms. Methods: Participants included 920 MLWH and 840 men without HIV infection from the Multicenter AIDS Cohort Study (MACS) with available data regarding glycaemic status [categorized as normal for fasting blood glucose (FBG) < 100 mg/dL, prediabetes for FBG 100–125 mg/dL, and diabetes, defined by self‐report, diabetes medication use or FBG ≥ 126 mg/dL on at least two consecutive visits, with diabetes classified as controlled if Hemoglobin A1c (HbA1C) < 7.5% and uncontrolled if HbA1C ≥ 7.5%]. Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression (CES‐D) score, with CES‐D ≥ 16 scores classified as elevated depressive symptoms. A modified Poisson regression model with robust variance was used and adjusted for covariates including HIV serostatus. Results: Compared to men without HIV infection, MLWH had a higher mean CES‐D score, but a similar prevalence of diabetes (11.3% versus 12.8%, respectively; P  = 0.33). The concomitant prevalence of diabetes and elevated depressive symptoms did not differ by HIV serostatus ( P  = 0.215). In an adjusted analysis, men with uncontrolled diabetes had a greater prevalence of depressive symptoms compared to men with normoglycaemia (prevalence ratio = 1.43; 95% confidence interval 1.11, 1.84). The association between glycaemic status and depressive symptoms did not differ by HIV serostatus ( P  = 0.22 for interaction). Conclusions: Both controlled and uncontrolled diabetes were independently associated with a greater prevalence of depressive symptoms, regardless of HIV serostatus. These results highlight the importance of identifying depression in people with diabetes.